Maternal and foetal outcome in COVID-19 infection: what we learnt and what lies ahead - Shaikh, Ambreen; Mayadeo, Niranjan; Dwivedi, Jyotsna; Mandlik, Madhura (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The world has seen 16 major pandemics since its inception. COVID-19 (coronavirus disease 2019), being the most recent one, was a pandemic the world faced, due to a new coronavirus called the SARS-CoV-2. It originated in Wuhan, China and soon grappled the whole world. The World Health Organization (WHO) declared COVID-19 a global pandemic on March 11, 2020. This pandemic lasted for three years, with the WHO finally declaring an end to the global health emergency on May 5, 2023 Pregnant women remain a vulnerable population for such respiratory illnesses that pose a risk to not only the mother but also the foetus. Methods: This was a retrospective study conducted in a tertiary care, premium institute in Mumbai, during the third wave of COVID 19 in India. Primary objective was to assess maternal and foetal outcome in COVID 19 positive patients. Secondary objective was to assess rate of preterm delivery in COVID 19 positive patients. Results: 103 COVID 19 positive women were included in the study. 74.7% patients who had tested positive, were asymptomatic. There was no statistical difference between the mode of delivery of patients. The most common comorbidity in the positive patients was pre-eclampsia (15.53%). 2.9% patients received Remdesivir and 2.9% received Favipravir. 58.2% were transferred to a dedicated COVID 19 hospital post-delivery. There were three intrauterine foetal demises. 18 (17.47%) women delivered preterm under 37 weeks. The rate of preterm delivery was significantly higher in COVID-positive patients (p-value <0.00025). Conclusions: The COVID-19 pandemic posed significant challenges for healthcare workers and policymakers. It is crucial for clinicians to learn from this experience to enhance preparedness and mitigate future adversities.